1967
DOI: 10.1039/tf9676301825
|View full text |Cite
|
Sign up to set email alerts
|

Conformational energies of perfluoroalkanes. Part 1.—Semi-empirical calculations

Abstract: Conformational energies have been calculated as functions of the internal rotation angles about the C-C bonds for n-perfluorobutane in the neighbourhood of its trans and gauche conformations, and for polytetrafluoroethylene (FTFE) in the vicinity of its all-trans form. The energy equation consists of a semi-empirical " 6-exp " potential for the interactions between non-bonded atoms, a dipole-dipole interaction term, and a three-fold " intrinsic " torsion potential having a barrier height Eo for each bond under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…That our equation (1) describes the disorder in Teflon fairly well is further supported by modelpotential-energy calculations (DeSantis, Giglio, Liquori & Ripamonti, 1963;McMahon & McCullough, 1965;Bates, 1967;Bates & Stockmayer, 1968) for free filaments which yield a relatively shallow potentialenergy well for rotations about the C-C bond. For T = 300 K, a shift of kT from the most stable bond angle (about 165 ° ) appears to be equal to about +8 ° (McMahon & McCullough, 1965, Fig.…”
Section: The Fourier Transform Of Actinmentioning
confidence: 60%
“…That our equation (1) describes the disorder in Teflon fairly well is further supported by modelpotential-energy calculations (DeSantis, Giglio, Liquori & Ripamonti, 1963;McMahon & McCullough, 1965;Bates, 1967;Bates & Stockmayer, 1968) for free filaments which yield a relatively shallow potentialenergy well for rotations about the C-C bond. For T = 300 K, a shift of kT from the most stable bond angle (about 165 ° ) appears to be equal to about +8 ° (McMahon & McCullough, 1965, Fig.…”
Section: The Fourier Transform Of Actinmentioning
confidence: 60%
“…Although the conformational characteristics of PTFE or Teflon (the predominant structure in the Nafion backbone) are well represented by a three-state model with rotation angles of one trans (φ = 0 o ) and two gauche (φ = ±115 o ) conformations, it has been shown that a four-state model is more physically accurate [3]. Therefore, this simulation adopts the four-state model with rotation angles of two trans (φ = ±15 o ) and two gauche (φ = ±120 o ) conformations.…”
Section: Rotational Isomeric Schemementioning
confidence: 99%
“…The values of σ = 0.2, σ = 2.0, ω = 0.2, and β = 0.5 were identified by comparing the mean of the range for each of the values provided in [3] to place the second bond of the backbone, U 3 to place the third bond of the backbone, and U N to place the last bond of the entire backbone chain. Hence U k is used to place bonds 4…”
Section: Statistical Weight Matricesmentioning
confidence: 99%
See 2 more Smart Citations